Odpowiedzi

2010-01-15T13:43:12+01:00
2 Cr( VI) +6e---> 2 Cr( III)
S( IV)- 2e---> S( VI) /*3
3 S( IV)- 6e----> 3 S( VI)

K2Cr2O7 + 4H2SO4 + 3Na2SO3 = Cr2(SO4)3 + K2SO4 + 3Na2SO4 + 4H2O
3 3 3
  • Użytkownik Zadane
2010-01-15T17:17:10+01:00
K₂Cr₂O₇ + H₂SO₄ + Na₂SO₃ --> Cr₂(SO₄)₃ + K₂SO₄ + Na₂SO₄ + H₂O

2Cr(VI)+6e --> 2 Cr(III) |*1
S(IV)-2e --> S(VI) |*3

2Cr(VI)+6e --> 2 Cr(III) |utleniacz
3 S( IV)- 6e----> 3 S( VI) |reduktor

K₂Cr₂O₇ + 4H₂SO₄ + 3Na₂SO₃ --> Cr₂(SO₄)₃ + K₂SO₄ + 3Na₂SO₄ + 4H₂O
_____________________________________________________________
Liczę na status najlepszego rozwiązania.
8 4 8